Studi Komparasi Strategi Talking Stick Dengan Think-Talk-Write (TTW) Terhadap Hasil Belajar Matematika Siswa Kelas V SDN Kacangan 1 Dan SDN Nganti 1 Tahun 2015/2016 - Sari, Mega Riana (2016)
The purpose of this research is 1) know different influence Talking Stick with Think Talk Write (TTW) strategy to outcome learning of mathematic for five grade SDN Kacangan 1 and SDN Nganti 1 2015/2016; 2) know strategy whom have more influence to out come learning of mathematic for five grade SDN Kacangan 1 and SDN Nganti 1 2015/2016. The Kind of this research is kuantitative experiment which two different class. Class ecperiment A with Talking Stick strategy and class experiment B with Think Talk Write (TTW) strategy. Calculation shown that t of calculate is 3,24 and t of tables with signification standard 95% is 2,00. So,Talking Stick strategy with Think Talk Write (TTW) strategy have different influence to out come learning of mathematic for five grade SDN Kacangan 1 and SDN Nganti 1 2015/2016. Average of out come learning mathematic Talking Stick strategy is 77,00, whereas Think Talk Write (TTW) strategy is 82,67. So, Think Talk Write (TTW) strategy have more influence to out come learning of mathematic for five grade SDN Kacangan 1 and SDN Nganti 1 2015/2016 in comparison with Talking Stick Strategy. Keyword: Talking Stick, Think Talk Write (TTW), Outcomes Learning of Mathematic